2018
DOI: 10.1002/acr.23465
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Response to Tumor Necrosis Factor Inhibitor Treatment in Axial Spondyloarthritis

Abstract: PLR accounted for nearly 40% of the TNFi failures in axial SpA patients. Older age, negative HLA-B27, higher baseline disease activity, and treatment with soluble TNF receptors were the independent predictors of the primary nonresponse to TNFi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…We report older age at initiation of TNFi as a predictor for sub-optimal response in axSpA. Younger age has been previously reported as a positive predictor for TNFi response [19, 20], whereas older age was reported as a predictor of non-response [10]. There are a number of reasons why older patients might be more susceptible to a sub-optimal response.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We report older age at initiation of TNFi as a predictor for sub-optimal response in axSpA. Younger age has been previously reported as a positive predictor for TNFi response [19, 20], whereas older age was reported as a predictor of non-response [10]. There are a number of reasons why older patients might be more susceptible to a sub-optimal response.…”
Section: Discussionmentioning
confidence: 64%
“…The rates of switching first TNFi owing to lack of or loss of efficacy range from 14 to 56% [9]. Older age, negative HLA-B27 and higher baseline BASDAI were reported as predictors of primary inefficacy of TNFi [10]. Although not universally effective for all patients, TNFi use may provide a degree of benefit for patients, which could subsequently influence the decision to continue treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Yahya et al (16) found no association between family history and 6 month BASDAI LDA or remission in British patients with axial SpA. Similarly, Alazmi et al (36) found no association between family history of SpA and 6 month BASDAI50 response in axial SpA patients in Canada. In RA, a related but less familial disease, family history was not associated with TNFi treatment outcome among Swedish patients (44).…”
Section: Discussionmentioning
confidence: 97%
“…Some have found lower age at onset (28)(29)(30)(31), increased prevalence of extra-articular manifestations or deformities (28,31), and increased disease activity in familial versus sporadic cases (28), while others found no such differences (32,33), or even milder disease in patients with familial SpA (29,34,35). The impact of family history on TNFi response at 6 months in axial SpA was investigated along with other potential predictors in two studies (16,36), where no association was found, but with family history data for only 349 and 249 patients, respectively, the power to detect clinically meaningful predictions was low. Thus, the impact of a family history of SpA on disease presentation and clinical outcomes, especially in relation to TNFi treatment, remains unclear.…”
mentioning
confidence: 99%
“…Nevertheless, generally we may assume that "stop failure" was assigned to possible activity of these manifestations. In the same sub-study, we could not control also for HLA-B27 status, which has been shown to influence TNFi response [414]. This examination was not routinely prescribed in Greece due to cost considerations and thus it was not available in most of the patients of the Registry.…”
Section: Chapter VIII Study Limitationsmentioning
confidence: 99%